Association of perfluorinated chemical exposure in utero with maternal and infant thyroid hormone levels in the Sapporo cohort of Hokkaido Study on the Environment and Children's Health. Issue 5 (September 2016) - Kato, Shizue; Itoh, Sachiko; Yuasa, Motoyuki; Baba, Toshiaki; Miyashita, Chihiro; Sasaki, Seiko; Nakajima, Sonomi; Uno, Akiko; Nakazawa, Hiroyuki; Iwasaki, Yusuke; Okada, Emiko; Kishi, Reiko
Abstract Objectives Perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) have been widely used as industrial products, and are persistent organic pollutants due to their chemical stability. Previous studies suggested that PFOS and PFOA might disrupt thyroid hormone (TH) status. Although TH plays an important role in fetal growth during pregnancy, little attention has been paid to the relationships between maternal exposure to perfluorocarbons and TH statuses of mothers and fetuses. We investigated the effects of low levels of environmental PFOS and PFOA on thyroid function of mothers and infants. Methods Of the eligible subjects in a prospective cohort, 392 mother–infant pairs were selected. Concentration of maternal serum PFOS and PFOA was measured in samples taken during the second and third trimesters or within 1 week of delivery. Blood samples for measuring thyroid stimulating hormone (TSH) and free thyroxine (FT4) levels were obtained from mothers at early gestational stage (median 11.1 weeks), and from infants between 4 and 7 days of age, respectively. Results Median concentrations of PFOS and PFOA were 5.2 [95 % confidence interval (CI) 1.6–12.3] and 1.2 (95 % CI limitation of detection–3.4) ng/mL, respectively. Maternal PFOS levels were inversely correlated with maternal serum TSH and positively associated with infant serum TSH, whereas maternal PFOA showed no significant relationship with TSH or FT4 among mothers and infants. Conclusions These findings suggest that PFOS may independently affect the secretion and balances of maternal and infant TSH even at low levels of environmental exposure.